Polynucleotides. XL. Synthesis and properties of poly 2'-azido-2'-deoxyadenylic acid. - Ikehara, M (1976)
Poly 2'-azido-2'-deoxyadenylic acid (Poly Az) was synthesized from 2'-azido-2'-deoxyadenosine diphosphate by polynucleotide phosphorylase. Poly (Az) has U.V. absorption properties similar to poly (A) and hypochromicity of 40% at 0.1 M Na+ and neutrality. CD curve also resembled to that of poly (A), but has smaller ellipticity. Titration of poly (Az) with HCl gave a transition at pH 5.5, but exact structure of the acid-form complex was not elucidated. Upon mixing with poly (U), poly (Az) forms a 1:1 and 1:2 complexes having Tm's somewhat higher than that of poly (A)- poly (U) complex in the same condition.